A bibliometric analysis of HIV nursing research between 1999 and 2022 - Jiaqi Hao; Qian Zhang; Xiaoyu Du; Fan Wang; Jing Liu; Jia Chen (Wiley, 2024)
Abstract Aim Human immunodeficiency virus (HIV) nursing has become more prominent with the increase in chronic HIV infections. This study examined articles related to HIV nursing to determine how the profession has developed and its future direction. Design A bibliometric analysis was conducted. Methods HIV nursing‐related articles published in the Web of Science core collection between 1999 and 2022 were searched. VOSviewer was used to identify the contributions of countries, institutions and authors in HIV‐related care. Collaborative maps, hot topics and keywords trends were analysed using VOSviewer and CiteSpace. Results A total of 1513 publications were extracted. An increase in articles published between 1999 and 2012 was observed. After 2012, the increase in the number of publications was relatively stable. Since 2016, a downward trend in the number of publications has occurred. The USA, South Africa and the UK were the leading contributors to publications related to HIV nursing. The focus of the HIV nursing research has gradually shifted from "HIV infection", "risk factors", and "transmission routes" to "social support", "depression", and "public health". The result shows that increased collaboration among countries/regions can improve the development of HIV nursing and effectively reduce the global HIV infection rate. The mental health of patients has become a research centre in the field of HIV nursing. This study provides direction in clinical practice and future research areas in this field.